Prolaction gene association with chicken egg production traits - FAN, JING; JIANG, LIN-LIN; LIU, XIAO-HUI; ZHANG, WEI-FENG; WANG, BIN; SHI, YU-XIANG; MA, TENG-HE (The Indian Journal of Animal Sciences, 2019)
In this study, using the direct sequencing technology, 6 SNPs were identified in PRL gene, among which, 3 SNPs were present in coding region and 3 in 3’UTR. Mutations in coding region did not change the protein sequences. SNPs g.4603, g.8823 and g.8885 were utilized for association test with AFE, EN 300 and EN 500. SNP g.4603 was associated with EN 300, whereas the SNP g.8823 was significantly associated with EN 300. These two SNPs in PRL gene could be used as the potential molecular markers for egg production traits selection in Taihang chicken.